Determinants of capital expenditure decisions : analysis of Malaysian listed companies within the managerial and pecking order hypotheses - Masyhuri Hamidi (2011)
This study examines Malaysian companies' decisions to invest in capital expenditure in the context of Managerial and Pecking Order Hypothesis. The main objective of this research is to determine the impact of internal cash flows, insider ownership, and investment opportunity on the capital expenditure decisions based on the two competing theories. The Pecking Order Hypothesis states that managers choose the level of capital expenditure that maximizes current shareholders' wealth regardless of their ownership stakes. On the other hand, the Managerial Hypothesis proposes that managers with relatively small ownership proportions tend to utilize higher level of internal cash flows to finance the capital expenditures than that which would maximize the wealth of the current shareholders. Thus, the Managerial Hypothesis predicts a negative relationship between the insider ownership and capital expenditure. It also suggests that investment opportunity does not affect capital expenditure. The Pecking Order Hypothesis, on the other hand, proposes a positive relationship between investment opportunity and capital expenditure since shareholders' wealth is maximized when managers optimize investment opportunities. However, this hypothesis predicts that the insider ownership does not affect capital expenditure. At the same time, both hypotheses are consistent in proposing that internal cash flow has a positive relationship with capital expenditure. This study focuses on manufacturing companies listed on Bursa Malaysia. The study period covers the year 2002 until 2006, and a total of 109 companies were chosen using purposive sampling. Therefore, the 5 year study period consists of 545 data. To test the hypotheses, multiple and ordered logistic regression models were used, where capital expenditure is categorized into five ordinal categories and the control variable is divided into four groups which are ranked to capture the variability of the capital expenditure variable. The data was analyzed using STATA program. The main findings of this research provide evidence that the internal cash flow has a positive and significant effect on capital expenditure and thus, supports both studied hypotheses. However, insider ownership and investment opportunity show a negative and significant effect on capital expenditure. Moreover, in the Malaysian context, the issue of conflicting interest between managers and shareholders does exist and the impact is significant. In conclusion, this empirical research reveals three interesting findings. Firstly, Malaysian manufacturers tend to finance their capital expenditures using internally generated cash flow rather than external debt. Secondly, even though managerial ownership in the Malaysian manufacturing companies is rather small, it does have a significant impact on the capital expenditure decisions. Finally, the negative relationship between investment opportunity and capital expenditure suggests the possibility that Malaysian companies rely mostly on internal cash flows to finance either capital expenditure projects or other investment opportunities. When both exist, there will be competition for internal cash flow and priority is given to other investment opportunity rather than capital expenditure projects.